Molecular modelling of the cannabinoid receptors: structure-based design, synthesis and pharmacological evaluation of novel ligands based on the fenofibrate scaffold - Loo, Jason S. E. (2015)
The cannabinoid receptors CB1 and CB2, which belong to the rhodopsin family of GPCRs, are implicated in the pathology of various disease states. As drugs targeting these receptors remain limited, novel cannabinoid receptor ligands represent an unmet need with substantial therapeutic potential. We present here the construction and application of homology models of the human CB1 and CB2 cannabinoid receptors based on the crystal structure of the human adenosine A2A receptor for the structure-based design of novel ligands based on the fenofibrate scaffold. Models were refined through molecular dynamic simulations in a lipid bilayer, and were validated via the prediction of known ligand binding affinities, enrichment studies and assessment of predicted ligand binding modes. These validated models were subsequently used in predicting the binding mode of fenofibrate derivatives to the cannabinoid receptors. The predicted binding mode of these fenofibrate derivatives to the CB2 receptor showed good agreement with known mutagenesis data, indicating the binding of these compounds to be stabilized primarily by hydrogen bonds with W5.43 and C7.42, aromatic stacking with F2.57, F3.36 and W6.48, and hydrophobic contact with F2.64, V3.32 and I5.47. A series of novel ligands was derived based on these findings, docked into our model, synthesized and pharmacologically evaluated at the CB2 receptor. The pharmacology of these ligands validated our modelling predictions and binding mode hypothesis, with several of these ligands showing unique pharmacology by binding in an allosteric manner. These findings may be used to guide the design of further derivatives and highlight the promise of the fenofibrate scaffold in the development of novel CB2 receptor ligands.